Mutual and Thermal Diffusivities in Polystyrene Melts with Dissolved Nitrogen by Dynamic Light Scattering - Piszko, Maximilian; Schaible, Tobias; Bonten, Christian; Fröba, Andreas Paul (Macromolecules, 2021)
Knowledge on diffusion coefficients in mixtures consisting of a polymer melt and a blowing agent is necessary for understanding and characterizing the bubble growth processes during foaming of thermoplastic polymers. Due to the lack of reliable literature data in process-relevant conditions, the diffusion coefficients are often assumed to be constant to solve the equations for bubble growth in polymer melts. This study demonstrates, for the first time, the applicability of dynamic light scattering for the characterization of molecular mass and thermal transport in binary mixtures consisting of a macromolecular polymer and a dissolved gas by the determination of mutual and thermal diffusivities in macroscopic thermodynamic equilibrium. In the present study, a mixture of polystyrene and nitrogen was selected as the model system, which has technical relevance. After evidencing that the obtained experimental signals are associated with hydrodynamic modes, the influence of pressure and temperature on mutual and thermal diffusivities is discussed and the results are compared with the literature. For the mixtures studied in this work, expanded experimental uncertainties (k = 2) of the obtained diffusivities have a minimum value close to 3% and are on average 13% for the thermal diffusivity and 7.4% for the mutual diffusivity.
CRIS-Team Scopus Importer:2021-07-02